Evidence-Based Practice and Sentencing in State Courts: A Critique of the Missouri System - Claire Botnick (Washington University Journal of Law & Policy, 2015)
This Note addresses the significant problem that is the United States’ criminal justice system as a whole, with a focus on the state of Missouri’s correctional practices. Specifically, it proposes that the use of evidence-based sentencing practices in Missouri, if done properly, could transform the state’s criminal justice system. Evidence-based sentencing methods use actuarial calculations and empirical research in judicial sentencing at decision making. This calculated approach is thought to help identify high- and low-risk offenders, reduce rising incarceration costs, as well as address a rising recidivism rate, and much more. Botnick argues that successful implementation of such practices in Missouri requires enhanced training for its users, ample resources put towards the implementation effort, increased transparency in data collection, and a limitation of the dynamic factors used in risk assessment tools.
Keywords: mass-incarceration; sentencing; corrections; prisons